2002
DOI: 10.1152/ajpheart.00290.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acute protection of ischemic heart by FGF-2: involvement of FGF-2 receptors and protein kinase C

Abstract: We examined the effect of fibroblast growth factor (FGF)-2 on myocardial resistance to injury when administered after the onset of ischemia , in vivo and ex vivo, and the role of FGF-2 receptors and protein kinase C (PKC). FGF-2 was injected into the left ventricle of rats undergoing permanent surgical coronary occlusion leading to myocardial infarction (MI). After 24 h, FGF-2-treated hearts displayed significantly reduced injury, determined by histological staining and troponin T release, and improved develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 48 publications
4
60
1
Order By: Relevance
“…The overexpression of both FGF-1 and FGF-2 have been shown to promote the survival of adult cardiomyocytes in response to ischemic injury in vivo (House et al, 2005;Jiang et al, 2002;Jiang et al, 2004;Palmen et al, 2004), and the cardioprotective effects of FGF-2 in the adult myocardium are mediated through the MAPK pathway (House et al, 2005), the same branch of the FGFR signaling cascade that we have shown in cardiac tissue functions through SHP-2. Interestingly, the specific function of FGF-2 in preventing programmed cell death in response to ischemic insult was shown to be independent of its mitogenic or angiogenic functions, suggesting that FGF-2 is functioning specifically to promote cardiomyocyte cell survival (Jiang et al, 2004).…”
Section: Shp-2 and The Fgf Pathwaysupporting
confidence: 53%
“…The overexpression of both FGF-1 and FGF-2 have been shown to promote the survival of adult cardiomyocytes in response to ischemic injury in vivo (House et al, 2005;Jiang et al, 2002;Jiang et al, 2004;Palmen et al, 2004), and the cardioprotective effects of FGF-2 in the adult myocardium are mediated through the MAPK pathway (House et al, 2005), the same branch of the FGFR signaling cascade that we have shown in cardiac tissue functions through SHP-2. Interestingly, the specific function of FGF-2 in preventing programmed cell death in response to ischemic insult was shown to be independent of its mitogenic or angiogenic functions, suggesting that FGF-2 is functioning specifically to promote cardiomyocyte cell survival (Jiang et al, 2004).…”
Section: Shp-2 and The Fgf Pathwaysupporting
confidence: 53%
“…In addition, increased levels of intracellular ATP during ischemia have been seen when recombinant FGF2 is administered to ischemic hearts (30). Further studies are currently determining whether depressed activity of contractile proteins mediated by PKC␣ during I/R may slow ATP depletion and intracellular calcium overload.…”
Section: Discussionmentioning
confidence: 99%
“…Snap-frozen nonischemic hearts (wild type) were powdered and homogenized in homogenization buffer (25 mM HEPES, pH 7.5, 1% glycerol, 150 mM NaCl, 1% Triton X-100, 5 mM EDTA, 1 mM sodium orthovandate, 25 mM ␤-glycerolphosphate, 50 mM sodium fluoride solid, 0.5 M okadaic acid, diisopropylfluorophosphate, 100 M calpain inhibitor, Pefabloc stock 1 and 2, and Sigma phosphatase inhibitor) as previously described (30,40,41). The homogenate was centrifuged at 13,000 g for 15 min, and the supernatant was collected.…”
Section: Whole Heart Preparation To Detect Fgfr Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of FGF-2 at the onset of ischemia is reported to reduce injury and attenuate heart enzymes. 17,18 It can be a promising choice of pretreatment in CABG to reduce the ischemic injury of cross-clamp time. Nakamae et al reported that FGF-2 enhanced vascular density in necrotic iliac bone in rabbits.…”
Section: Discussionmentioning
confidence: 99%